DataCite: The International Data Citation Initiative. Datasets programme - Max Wilkinson (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2010)
DataCite is an international consortium which aims to increase acceptance of research data as legitimate, citable contributions to scholarly communication. To enable this DataCite assigns persistent identifiers for research datasets and manages the infrastructures that support simple and effective methods of data citation, discovery and access. DataCite leverages the DOI infrastructure, which is already well-established. DOI names are the mostly widely used identifier for scientific journal articles, so researchers, authors, and publishers are familiar with their use. DataCite takes an open approach, however, and considers identifier systems and services that help forward its objectives. DataCite is represented in the UK by the British Library. This summary of the British Library's involvement in DataCite was presented to the UK data Forum on Monday the 15th November 2010. Data publishers that wish to know more about DataCite or to use DataCite services are encouraged to contact the Library or their local DataCite members.
Keywords: 330